Separação e purificação do ácido clavulânico através de extração líquido-líquido seguida de adsorção em coluna de leito fixo - Brites, Luciana Machado (2005)
A study was made of the extraction of clavulanic acid (CA) from a fermented medium and its concentration and purification, based on a comparison of two liquid-liquid extraction methods, followed by adsorption in a fixed bed column containing resins (hydrophobic polymeric resin and ion exchange resin). The extraction and adsorption steps proposed here were evaluated from the standpoint of Yield (Y), purification factor (PF) and concentration factor (CF). The extractions were carried out with the organic solvents ethyl acetate, butyl acetate, 2-butanol, n-butanol and methyl isobutyl ketone. These extractions were carried out at ambient temperature, pH values of 2.0, 3.0, 4.0 and 5.0 and with different volume ratios of aqueous phase and organic phase (VAF/VOP). After extraction with the organic solvent, the solution was reextracted with a phosphate buffer solution. Extractions were also done with two-phase aqueous systems (TPAS) composed of polyethylene glycol (PEG) and phosphate. The experimental conditions were: ambient temperature, pH of 6.0 and 7.0, and different molecular weights of PEG (400, 600, 4000). For the extractions involving organic solvents, an evaluation was made of the purification of clavulanic acid by ion exchange adsorption with Amberlite IRA-400 resin in a fixed bed column at a temperature of 10°C and pH 6.2. After adsorption by ion exchange, the column was washed with Milli-Q water and the elution was studied with different compositions of a solution composed of NaCl 5% (p/v) and Tris-HCl. The elution was carried out at pH 6.2 and a feed flow of approximately 6 mL.min-1. The solution eluted from the ion exchange was fed into a column filled with Amberlite XAD-4 resin at a temperature of 10°C and pH of 6.2. For the TPAS extractions, the application of ion exchange and nonspecific adsorption with Amberlite XAD-4 resin for the separation of CA from PEG was evaluated separately.